PENGARUH KODE ETIK, KOMPETENSI, DAN PENGALAMAN TERHADAP SKEPTISME PROFESIONAL AUDITOR (STUDI KASUS PADA INSPEKTORAT PROVINSI BENGKULU) - Asmil Darafni; , fadli; , Praningrum (Unib Press Universitas Bengkulu, 2017)
The purpose of this research is to know the influence of ethical code; competency and experience towards professional sceptic of auditors in the Inspectorate Office of Bengkulu Province by simultaneously and partially. The sample in this research are auditors of Inspectorate Office of Bengkulu Province taken usingcensus method. The number of respondents are 46 respondents. The method of the data analysis used was multiple regression analysis. The results from the data analysis show that: (1) the ethical code; competency and experience have positive and significant influence towardsprofessional sceptic of auditors at the Inspectorate of Bengkulu Province; (2) the ethical code have positive and significant influence towardsprofessional sceptic of auditors at the Inspectorate of Bengkulu Province; (3) the competency have positive and significant influence towardsprofessional sceptic of auditors at the Inspectorate of Bengkulu Province; and (4) the experience have positive and significant influence towardsprofessional sceptic of auditors at the Inspectorate of Bengkulu Province. Its mean if the ethical code, competency and experience have increasing, the professional sceptic of auditors at the Inspectorate of Bengkulu Province will be higher.